Pengaruh Mengonsumsi Buah Pepaya Terhadap Kelancaran Produksi Asi Pada Ibu Menyusui Bayi Usia 0-6 Bulan Di Desa Pasir Utama Kec. Rambah Hilir Kab. Rokan Hulu - Heny Sepduwiana; Rika Herawati; Eka Yuli Handayani; Andria Andria; Sevina Herawati (Journal of Innovative and Creativity, 2025)
Providing exclusive breast milk (ASI) is the right nutrition for babies aged 0-6 months. Exclusive breastfeeding coverage in Indonesia from now on in 2022 has not yet reached a satisfactory target. One of the causes of this failure is poor breast milk production. The production and release of breast milk is influenced by the hormones prolactin and oxytocin, while the hormone prolactin is closely related to the type of nutrition consumed. One type of nutrition that can increase breast milk volume is papaya, because papaya contains lactogogum which can facilitate breast milk. The aim of this research was to determine the effect of consuming papaya in increasing the volume of breast milk in breastfeeding mothers. This research is a pre-experiment with a one group pre-test and post-test design. The sample used was 15 people. This research method uses measurements of breast milk volume before and after consuming 600 grams of papaya fruit in 7 days. Data were analyzed via t-dependent test. The results of the T test analysis showed that the p value was 0.000 < 0.05, so that the research results could be concluded that there was an effect of consuming papaya on the smoothness of breast milk in mothers breastfeeding babies aged 0-6 months in Pasir Utama Village. In this way, it is hoped that it will be useful and add information and input materials in an effort to improve information and the quality of health services and motivate breastfeeding mothers to consume papaya for smooth breastfeeding. Keywords: Breastfeeding Mothers, Smooth Breastfeeding, Papaya Fruit